2019
DOI: 10.3390/pr7020060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supercritical Fluid Extraction Process on Chemical Composition of Polianthes tuberosa Flower Extracts

Abstract: Supercritical fluid extracts from flowers of Polianthes tuberosa var. double were ob tained using carbon dioxide as a solvent. Yield extract obtained was 2.5%. The effects of the pressure process (18 MPa, 28 MPa, and 38 MPa) and temperature process (313 K, 323 K, and 333 K) on the volatile composition of tuberose flowers extracts were evaluated, and a significant variation in chemical composition was found. Characteristic compounds of tuberose as methyl isoeugenol, benzyl benzoate, methyl anthranilate, pentaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Figure 3. Organic extract extraction methods: (a) supercritical fluid extraction, (b) cold pressing-assisted supercritical fluid extraction, (c) ultrasound-assisted supercritical fluid extraction, (d) ultrasound-assisted extraction, (e) microwave-assisted extraction, and (f) ohmic heating-assisted extraction (Hatami et al[20] and Fragoso-Jiménez et al[51]). …”
mentioning
confidence: 99%
“…Figure 3. Organic extract extraction methods: (a) supercritical fluid extraction, (b) cold pressing-assisted supercritical fluid extraction, (c) ultrasound-assisted supercritical fluid extraction, (d) ultrasound-assisted extraction, (e) microwave-assisted extraction, and (f) ohmic heating-assisted extraction (Hatami et al[20] and Fragoso-Jiménez et al[51]). …”
mentioning
confidence: 99%
“…The GC-MS analysis of the extracts obtained from the ovary, petal, and stamens showed the presence of additional phytochemicals such as piperonal, vanillin, [14] used a supercritical extraction procedure to identify the photo components from the flower of P. tuberosa by GC-MS. The authors reported the presence of 37 compounds, mainly volatile compounds like terpenes, hydrocarbons, alcohols, and esters from the whole flower.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Supercritical fluid extraction comprises a known technology applied to obtain volatile compounds from flowers, i.e., tuberose (belonging to the Asparagaceae family), that could be used for example in the perfume or fragrance industry [1]. The cocoa shell-a residue of low commercial value-represents an alternative for obtaining substances of added value for the food and pharmaceutical industry, including fat, theobromine and caffeine [2].…”
mentioning
confidence: 99%